PENGARUH MEDIA PEMBELAJARAN FLASH CARD TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS V SDN PONDOK BAHAR 3 - Aida Nabila; Dilla Fadhillah; Boy Dorahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Discussing facts and opinions in Indonesian language lessons often makes the classroom atmosphere feel rigid. To break this pattern, Flash Cards come as a simple yet powerful medium that sparks learning interactions. With their colors, images, and easy-to-remember format, Flash Cards are expected to boost motivation and help students clearly distinguish between facts and opinions. A quasi-experimental design with a Nonequivalent Control Group Design was applied in this study, involving 66 fifth-grade students of SDN Pondok Bahar 3 in the 2024/2025 academic year. Class VA served as the experimental group using Flash Cards, while Class VB acted as the control group. The research instrument consisted of 25 multiple-choice questions that had been validated to measure learning outcomes. Data analysis using a t test revealed that the pretest results showed no significant differences, while the posttest indicated a meaningful gap with a t value of 2.977 higher than the t table of 1.997. These findings confirm that Flash Cards are not merely colorful pieces of paper, but a creative strategy that strengthens comprehension and enhances student achievement in learning facts and opinions.